Establishment of the microscope incubation system and its application in evaluating tumor treatment effects through real-time live cellular imaging - Yan, Haiyang; Wu, Tong; Li, Xinlu; Feng, Zhengyang; Ge, Mingfeng; Zhang, Lixing; Dong, Wen-Fei (Frontiers in Bioengineering and Biotechnology, 2024)
Long-term imaging of live cells is commonly used for the study of dynamic cell behaviors. It is crucial to keep the cell viability during the investigation of physiological and biological processes by live cell imaging. Conventional incubators that providing stable temperature, carbon dioxide (CO2) concentration, and humidity are often incompatible with most imaging tools. Available commercial or custommade stage-top incubators are bulky or unable to provide constant environmental conditions during long time culture. In this study, we reported the development of the microscope incubation system (MIS) that can be easily adapted to any inverted